Peluang Edupreneurship Bagi Kesejahteraan Guru Di Indonesia - Kasidi, Daniel (Tractare: Jurnal Ekonomi-Manajemen, 2023)
It is undeniable that teachers are the driving force of the education system in Indonesia. But the welfare of teachers is still relatively small. The heavy workload is not proportional to the income received by each teacher. As a result, teachers must be able to see opportunities to improve their welfare. The concept of edupreneurship, combines elements of entrepreneurship into elements of education, become one of the things that Indonesian teachers deserve to pursue. This study aims to see edupreneurship opportunities in improving teacher welfare. The research method used is a literature study on 14 researches from 2018 to 2023. And this study result tell the concept of edupreneurship has a great and positive opportunity to improve teacher welfare in Indonesia.